2016
DOI: 10.1097/grf.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic High-risk Lesions, Diagnosis and Management

Abstract: Percutaneous imaging-guided core needle biopsy (CNB) is a less invasive and less expensive alternative to surgical biopsy for the evaluation of breast lesions. After a CNB the radiologist determine if there is concordance between the pathology, imaging and clinical findings. Patient management after CNB diagnosis of high risk breast lesion varies. Surgical excision is warranted for lesions yielding a CNB diagnosis of ADH; however controversy exists regarding the need for surgical excision after CNB diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…A review of the available literature shows that ADH is often associated with a significantly higher risk of concomitant DCIS and/or invasive carcinoma (IC) diagnosed by subsequent surgical excisions [ 5 , 6 , 7 , 8 , 9 ]. Although debate on this subject still exists, the diagnosis of ADH is an indication for surgery [ 3 , 6 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the available literature shows that ADH is often associated with a significantly higher risk of concomitant DCIS and/or invasive carcinoma (IC) diagnosed by subsequent surgical excisions [ 5 , 6 , 7 , 8 , 9 ]. Although debate on this subject still exists, the diagnosis of ADH is an indication for surgery [ 3 , 6 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…1, 16 AH is a major precancerous lesion, 17 and early treatment and monitoring during this important pathological stage can have significant impacts on the incidence of breast cancer. 5 However, the current large-scale epidemiological investigation showed that breast AH cannot be diagnosed and monitored accurately based on clinical features and risk factors. AH is characterized by filling and distention of the involved ducts by monotonous epithelial cells forming architecturally complex patterns, including cribriform-like secondary lumens or micropapillary formations.…”
Section: Discussionmentioning
confidence: 99%
“…The breast cancer progression model introduced by Wellings and Jensen 4 initially suggested that normal cells in the terminal ductal lobular unit first progress to atypical hyperplasia (AH), then develop into ductal carcinoma in situ, and finally to invasive carcinoma. Preventing the malignant transformation of breast AH cells could significantly decrease the occurrence of cancer, 2,5 and understanding the pathologic stage of AH is thus extremely important in terms of the clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…La denominación de cicatriz radial por lo regular se usa en lesiones de hasta 1 cm (una de mayor tamaño es lesión esclerosante compleja). 9,10 Su diagnóstico era incidental en la evaluación microscópica, pero recientemente su sospecha ha aumentado por mayor acceso a la mamografía 11,12 en la que se presenta como un área de distorsión arquitectónica, 5 acompañada de otros criterios: 1) presencia de una radiolucidez central, 2) espículas radiadas delgadas, largas, 3) apariencia diferente según las proyecciones, 4) estructuras lineales radiolúcidas paralelas a las espículas y 5) ausencia de lesiones palpables o cambios en la piel. 13 En el ultrasonido son visibles como masas hipoecoicas irregulares con sombreado posterior prácticamente idénticas al aspecto del cáncer de mama.…”
Section: Discusionunclassified